Determinants, persistence and value implications of liquidity creation: an evidence from Indian banks. Issue 2 (11th February 2021) - Grover, Naina; Sinha, Pankaj
Abstract : Purpose: The purpose of this paper is to explore the micro and macro factors affecting liquidity creation by scheduled commercial banks (excluding Regional Rural Bank) in India from 2005 to 2018. Design/methodology/approach: Two measures of liquidity creation, the broad and narrow measures, are constructed using RBI data available on Indian banks. System generalized method of moments has been applied to explore the factors affecting liquidity creation. Findings: This study finds high level of persistence in liquidity creation in banks. Variation in the broad measure is explained by equity ratio, market share, GDP, gross savings and lending rate, whereas the narrow measure is explained by equity ratio, market share, size and lending rate. The Global Financial Crisis had a negative effect on liquidity creation as per both the measures, and the impact was more severe for the broad measure as compared to the narrow measure. Research limitations/implications: This study finds a positive correlation between bank value and liquidity creation which suggests that the investors favourably evaluate banks that create more liquidity. This study is confined to India only. Practical implications: There is a negative influence of capital on liquidity created by banks, which implies a trade-off that exists between financial stability and liquidity creation. Basel III norms impose higher capital and liquidity standards which will have negative implications for liquidity creation. Originality/value: To the best of authors' knowledge, this is the first study in the Indian context that focusses on factors affecting liquidity creation in a dynamic framework and determines the relationship between liquidity creation and market value of a bank.